ASC filament formation serves as a signal amplification mechanism for inflammasomes - Mathias S. Dick (Nature Portfolio, 2016)
Inflammasomes regulate IL-1β family maturation and pyroptosis. Here the authors show that ASC oligomerization and the formation of ASC specks are needed for IL-1β processing, but are not required for pyroptosis, indicating distinct inflammasome regulatory pathways.